Individualized home-based exercise programs for older people to reduce falls and improve physical performance: A systematic review and meta-analysis. Issue 1 (September 2015) - Hill, Keith D.; Hunter, Susan W.; Batchelor, Frances A.; Cavalheri, Vinicius; Burton, Elissa
Highlights Individualized home-based exercise can reduce falls and improve physical performance. Samples included increased falls risk, Parkinson's disease, hip fracture and dementia. Older people discharged from hospital do not appear to benefit from this intervention.